PERTANGGUNGJAWABAN KERUGIAN NEGARA DALAM PENGELOLAAN KEUANGAN DAERAH - Karianga, Hendra (EDUKASI, 2018)
Sources of revenue and expenditure of APBD (regional budget) can be allocated to finance the compulsory affairs and optional affairs in the form of programs and activities related to the improvement of public services, job creation, poverty alleviation, improvement of environmental quality, and regional economic growth. The implications of these policies is the need for funds to finance the implementation of the functions, that have become regional authority, is also increasing. In practice, regional financial management still poses a complicated issue because the regional head are reluctant to release pro-people regional budget policy, even implication of regional autonomy is likely to give birth to little kings in region causing losses to state finance and most end up in legal proceedings. This paper discusses the loss of state finance and forms of liability for losses to the state finance. The result of the study can be concluded firstly,Â  there are still many differences in giving meaning and definition of the loss of state finace and no standard definition of state losses, can cause difficulties. The difficulty there is in an effort to determine the amount of the state finance losses. The calculation of state/regions losses that occur today is simply assessing the suitability of the size of the budget and expenditure without considering profits earned by the community and the impact of the use of budget to the community. Secondly, the liability for losses to the state finance is the fulfillment of the consequences for a person to give or to do something in the regional financial management by giving birth to three forms of liability, namely the Criminal liability, Civil liability, and Administrative liability.Keywords: state finance losses, liability, regional finance.